1999
DOI: 10.1080/713803517
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Nuclear Matrix and Associated Proteins that Bind the Haptoglobin Gene Cis‐Element

Abstract: SummaryTo identify the major nuclear matrix proteins that bind to the rat haptoglobin gene cis-element, we isolated a soluble nuclear matrix protein fraction and analysed it by gel retardation. Two major DNA-binding proteins exhibiting different types of protein-DNA interactions were detected: a DNA sequence-speci c 32-kDa isoform of transcription factor C/EBP¯, and a nuclear matrix protein p55 that bound to the DNA nonspeci cally. During increased transcription of the haptoglobin gene in the course of the acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…These ndings are in agreement with the increasing body of evidence demonstrating that different regulatory proteins are components of the nuclear matrix (22,(25)(26)(27)(28)(29)(30)(31)(32). The dynamic interactions of C/EBPa and PCNA with the nuclear matrix during liver development lend further support to the concept that the nuclear matrix facilitates gene expression by concentrating and localizing regulatory proteins near their target sites.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…These ndings are in agreement with the increasing body of evidence demonstrating that different regulatory proteins are components of the nuclear matrix (22,(25)(26)(27)(28)(29)(30)(31)(32). The dynamic interactions of C/EBPa and PCNA with the nuclear matrix during liver development lend further support to the concept that the nuclear matrix facilitates gene expression by concentrating and localizing regulatory proteins near their target sites.…”
Section: Resultssupporting
confidence: 77%
“…Recently we reported an increase in DNA-binding af nity and concentration of the nuclear matrix-bound transcription factor C/EBPb during the acute-phase reaction (22). Given that expression of C/EBPa is induced during development and that it regulates hepatocyte proliferation in newborn mice (9), we pursued the association of C/EBPa with the nuclear matrix.…”
Section: Resultsmentioning
confidence: 99%
“…It has already been suggested that nonspeci c protein-DNA interactions could be the initial interaction in the process of facilitated location of speci c target sites (34,35). We suggested previously that the nuclear matrix undergoes a three-dimensional readjustment at the point of contact with chromatin during the AP reaction (16). This assumption was based on the observed changes of interaction of the 5 0 region of the haptoglobin gene with nuclear matrix proteins, the posttranslational modi cations of the DNA-binding lamins and p55, and the increased partitioning of p55 on the nuclear matrix.…”
Section: Resultsmentioning
confidence: 99%
“…Also involved in the binding were a nuclear matrix protein designated as p55 and lamins A and C (15). The determining factors for the observed increased af nity were the AP-induced posttranslational glucosylation, phosphorylation, and an increased partitioning of p55 on the nuclear matrix (16). In the present work, we have extended our examination of DNA-binding nuclear matrix proteins to the rat haptoglobin gene hormone-responsive cis-element (17), using an electrophoretic mobility shift assay (EMSA) and nonisotopic identi cation of the formed nucleoprotein complexes by silver staining.…”
Section: Introductionmentioning
confidence: 99%
“…Re-electrophoresis was performed to separate and identify the proteins in the nucleoprotein complexes according to their molecular masses by SDS-PAGE [Poznanović et al, 1999]. Two gels were always run simultaneously during EMSA.…”
Section: Re-electrophoretic Analysis Of the Nucleoprotein Complexes Omentioning
confidence: 99%